Gas Transmitters (CO and NO) as Factors Regulating the Skin Cells Functions - KOZIOROWSKA, ANNA; ROMEROWICZ-MISIELAK, MARIA (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2017)
The paper presents the results of research conducted on cells isolated from the epidermal layer of the skin taken from the ear of domestic swine (Sus scrofa). It was checked whether the increase in the concentration of carbon monoxide (CO) in cell culture, cause changes in their viability, and will affect the changes in the production of nitric oxide. For evaluation of the viability of cells, the MTT assay was used. The concentration of a nitric oxide metabolites (NO3/NO2), in the cell supernatants was measured using test-Measure iT High-Sensitivity Nitrite Assay Kit.